Analysis of Occupational Hazard and Risk Identification Using the Job Safety Analysis Method - Hummah, Wardhatul; Nizwardi Azkha; Yulia (Jurnal Kesehatan Cendikia Jenius, 2025)
Occupational safety and health (OSH) is a major priority in the energy sector, including PT PLN. Data from the Ministry of Manpower (2024) reported 162,327 occupational accidents in Indonesia, with 91.83% involving wage workers. This study aimed to analyze hazard identification and risk assessment using the Job Safety Analysis (JSA) method at PT PLN UP3 Padang in 2025. The research employed a qualitative descriptive approach through in-depth interviews with seven informants, field observations, and JSA document reviews. Data were analyzed using source and technique triangulation and risk relative calculations. The findings revealed three high-risk activities: pole installation/replacement, household connections, and distribution network maintenance. Extreme hazards identified include electric shock, falls from height, musculoskeletal disorders, heat stress, extreme weather, and challenging terrain. Risk control measures should include strict supervision, mandatory Lockout Tagout (LOTO) procedures, and digital technology utilization. This study recommends regular JSA evaluations, continuous OSH training, improved personal protective equipment availability, and real-time hazard reporting systems to minimize accidents.